Interference of speed at cutting height and damage to rootstock in mechanical harvesting of sugarcane - Martins, Murilo Battistuzzi [UNESP]; Testa, João Vitor Paulo [UNESP]; Drudi, Fernanda Scaranello [UNESP]; Sandi, Jefferson [UNESP]; Ramos, Carlos Renato Guedes [UNESP]; Lanças, Kléber Pereira [UNESP] (Southern Cross Publishing, 2019)
In the mechanized harvest, the quality of the basal cut becomes one of the most important factors because it is associated with sprouting of the cane field. The objective of this work was to evaluate the influence of speed at cutting height and damage to the rootstock in function of mechanized harvesting of sugarcane. The variety used was CTC 15, with an average yield of 92.5 t ha-1. The mechanized harvest was conducted without previous burning of the cane field, in an area with a slope of 6% and a spacing of 1.5 meters between rows of planting. Three speeds were selected for movement of the harvester: V1: 3.0, V2: 5.0 and V3: 7.0 km h-1, performed with four replications. The evaluation of the quality of the mechanized harvest in relation to the basal cut was determined with the evaluation of the remaining stumps and the damages caused to rootstocks after the passage of the harvester. The height of cut was measured with a tape measure. For the damages to rootstocks, the chi-square test was applied. The cut height measurements were submitted to ANOVA and the averages were analyzed by Tukey test at 5% probability. The results showed that increase in speed during the operation of mechanized harvesting of sugarcane increased the average height of cut in evaluated treatments, as well as the damages to rootstocks which was higher according to the increase in the speed of the harvester. The increase in the speed of displacement of the sugarcane harvester influenced the height of the cut and the damage to the rootstock.
Keywords: Mechanization; Quality; Saccharum spp